Printing photovoltaics by electrospray - Zhao Xinyan (Institue of Optics and Electronics, Chinese Academy of Sciences, 2020)
Solution processible photovoltaics (PV) are poised to play an important role in scalable manufacturing of low-cost solar cells. Electrospray is uniquely suited for fabricating PVs due to its several desirable characteristics of an ideal manufacturing process such as compatibility with roll-to-roll production processes, tunability and uniformity of droplet size, capability of operating at atmospheric pressure, and negligible material waste and nano structures. This review begins with an introduction of the fundamentals and unique properties of electrospray. We put emphasis on the evaporation time and residence time that jointly affect the deposition outcome. Then we review the efforts of electrospray printing polymer solar cells, perovskite solar cells, and dye sensitized solar cells. Collectively, these results demonstrate the advantages of electrospray for solution processed PV. Electrospray has also exhibited the capability of producing uniform films as well as nanostructured and even multiscale films. So far, the electrospray has been found to improve active layer morphology, and create devices with efficiencies comparable with that of spin-coating. Finally, we discuss challenges and research opportunities that enable electrospray to become a mainstream technique for industrial scale production.